The welfare loss from differential taxation of sectors in Germany - Doina Maria Radulescu; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2008)
In the spirit of Harberger, we apply a dynamic computable general equilibrium (CGE) model and estimate the excess burden stemming from the tax-induced distortion in the allocation of capital across the corporate and the non-corporate sectors in Germany. In doing so, we perform a counterfactual analysis and ask how the allocation of capital across sectors would change compared with a sector-neutral tax system which assures an identical effective tax burden on both sectors. Our estimates suggest that the excess burden per period ranges from 2.0 to 3.6 billion Euros or from about 0.1 to 0.16 per cent of GDP. In present value terms, the excess burden translates to about 104 billion Euros or 4.7 per cent of GDP. In order to identify the impact of the firm's financial behaviour on the size of the emerging excess burden, we perform several sensitivity analyses with regard to debt financing, external equity financing and debt constraints via agency cost.
Keywords: C68; C87; D92; H25; 330; Capital income taxation; non-uniform taxation; computable general equilibrium modelling; Kapitalertragsteuer; Unternehmensbesteuerung; Branche; Excess Burden; Steuerwirkung; Finanzierung; Dynamisches Gleichgewicht; Theorie; Deutschland